Pengaruh Razia Lapangan, Kesadaran Wajib Pajak, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kantor Samsat Kota Ambon - Juwilda Febrianti; Cecilia Engko; Alfrin Ernest Marthen Usmany (CV. ALIM'SPUBLISHING, 2024)
This research aims to empirically test the influence of field raids, taxpayer awareness and tax sanctions on motor vehicle taxpayer compliance.The data source used in this research is primary data through the results of distributing questionnaires to motor vehicle taxpayers at the Ambon City Samsat Office. The total sample in this research was 100 taxpayers using a convenience sampling technique. The data collection technique uses a questionnaire and the data analysis used to test the hypothesis is multiple linear regression analysis.The results of this research show that field raids have a positive effect on the level of motor vehicle taxpayer compliance in Ambon City, taxpayer awareness has a positive effect on the level of motor vehicle taxpayer compliance in Ambon City, and tax sanctions have a positive effect on the level of motor vehicle taxpayer compliance in Ambon City. Ambon City.